Rethinking development and sustainability of African economy: The roles of science education - Oloruntegbe, K.O.; Akinsete, A.M.; Ayeni, E.O.; Odutuyi, M.O.; Alam, G.M. (Academic Journals, 2010)
It is an understatement that of all the continents in the world Africa is seriously lagging behind in the area of development and sustainability. Trend studies of vital indices revealed a slow pace of development, which portends a great danger for the continent coupled with it being bedeviled by political instability. This study offers a rethink of these situations and the roles science education could play in fostering the much-needed development in Africa. The areas of focus are food security, energy supply, institutional infrastructures, education, health and environmental conscious designs. Conclusions are drawn and recommendations made on the ways forward.